Analysis of Physical Education Learning Motivation Based on Gender Perspective at State Senior High School 2 Majalaya - Mufiidah Butsainah Afiyah; Reshandi Nugraha; Riansyah Riansyah (Universitas Negeri Semarang, 2025)
This study aims to investigate the motivations for learning Physical Education, Sports, and Health (PE) among high school students from a gender perspective. The basis of this study is the importance of motivation as a key factor in student engagement, persistence, and academic achievement. This study is distinct from prior research, predominantly conducted at the elementary and junior high school levels, as it concentrates on high school and employs the Indonesian version of the Academic Motivation Scale (AMS) instrument, validated for its reliability and validity.. This research adopts a descriptive quantitative methodology, with a sample selected through stratified random sampling, including both male and female students from State Senior High School 2 Majalaya. Data analysis was carried out through descriptive tests, normality tests, non-parametric Mann-Whitney tests, and effect size tests. The results showed no significant differences in PE learning motivation between male and female students. This finding is reinforced by the very Senior High School effect size, so the role of gender on learning motivation can be said to be limited. Thus, student learning motivation is more influenced by external factors such as learning methods, teacher support, and the learning environment. This research is expected to contribute to the literature on PE learning motivation as well as practical recommendations for teachers in designing more inclusive learning.